Primary Angioplasty without Stenting for Symptomatic, High-Grade Intracranial Stenosis with Poor Circulation - Wang, Y.; Ma, Y.; Gao, P.; Chen, Y.; Yang, B.; Jiao, L. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Although the Stenting versus Aggressive Medical Management for Preventing Recurrent Stroke in Intracranial Stenosis (SAMMPRIS) study demonstrated a high incidence of perioperative complications for Intracranial Atherosclerotic disease (ICAD) treatments with stent placement, some studies have shown that submaximal angioplasty with an undersized balloon limits the risks of perioperative complications, suggesting that intervention may remain an alternative option for ICAD if perioperative complications are minimized. We sought to evaluate clinical and angiographic outcomes after primary angioplasty without stent placement in patients with symptomatic, high-grade intracranial stenosis and poor antegrade flow who were refractory to medical therapy.MATERIALS AND METHODS: All cases with high-grade, symptomatic intracranial stenosis and poor antegrade flow treated with intracranial angioplasty without stent placement at Xuanwu Hospital, Capital Medical University, from January 2010 to December 2016, were retrospectively reviewed. The main outcomes included the changes in antegrade flow and residual stenosis and any stroke or death within 1 month. We also evaluated functional outcomes, stroke, and restenosis in patients on follow-up.RESULTS: Thirty-five patients (mean age, 64.3 years) were included, and the mean follow-up time was 9.7 months. The average preprocedural stenosis was 88.4%. The immediate, average postprocedure stenosis rate was 25.3%, and the average postprocedural stenosis rate at last angiographic follow-up was 34.7%. The primary end point of major stroke or death at 30 days was observed in 1 patient (1/35, 2.9%), and no patient had intraprocedural complications. The incidence of stroke or death at the last follow-up was 2.9%, which was superior to the results of the medical and stent-placement arms of the SAMMPRIS study. Severe restenosis was observed in 3 (3/25, 12%) patients but without any symptoms.CONCLUSIONS: In this retrospective series, primary balloon angioplasty was an effective treatment option for symptomatic intracranial stenosis with a high risk of stroke.SAMMPRISStenting versus Aggressive Medical Management for Preventing Recurrent Stroke in Intracranial Stenosis